Study the structural and Optical properties of ZnO thin film - Abdul Majeed E.Ibrahim; Raid A. Isma'el; Enad S.Ibrahim; Essam M.Ibrahim (Tikrit Journal of Pure Science, 2023)
This research included preparation of ZnO thin films from Zinc acetate solution (Zn(CH3COO)22H2O). on glass substrate with dimension (2.5cmx2.5cmx0.1cm) using chemical spray pyrolysis method composed with (0.2M). The structural properties were characterized by X-Ray diffraction (XRD), Atomic force microscope (AFM), Scanning electron microscope (SEM) and Energy dispersive of X-Ray (EDX). The film grown have a polycrystalline wurtizte structure it can be seen that the highest texture coefficient was in (002) plane. So (AFM) measurement show that the roughness average (1.51nm), root mean square (RMS = 1.75nm) and dimeter average (108.96nm). The optical properties were characterized by (UV- Visible) and showed that higher transmittance about (97%) and optical Energy gab (Eg=3.28 eV).